Epidemiological characteristics and trends of Bacillus Calmette-Guérin lymphadenitis in Shanghai, China from 2010 to 2019 - Jing Wang; Feng Zhou; Ming-Bo Jiang; Zhen-hui Xu; Yi-hong Ni; Qiang-Song Wu (Taylor & Francis Group, 2022)
Although the administration of the Bacillus Calmette-Guérin (BCG) vaccine is generally safe, lymphadenitis, the most common complication of BCG vaccination, can occur. Here, we describe the epidemiological characteristics and incidence trends of BCG lymphadenitis in Shanghai, China, among a population with a high burden of tuberculosis. A total of 56 cases of adverse events following immunization (AEFI) after BCG vaccination were reported in Shanghai, including 51 cases of BCG lymphadenitis (91.07%), from 2010 to 2019. The general incidence of BCG lymphadenitis was 173 per 1,000,000 doses in Shanghai from 2010 to 2019. A nonsignificant increase of 58.81% per year was observed between 2010 and 2012 (t = 0.93; p = .40), followed by a significant decline of 28.00% per year from 2012 to 2019 (t = −4.27; p < .01). Seven batches of BCG vaccines triggered three or more BCG lymphadenitis cases, for 27 (52.94%) cases in total. We identified two patients with immunodeficiency of chronic granulomatous disease, one of whom died four years later after BCG vaccination and another of whom was still being treated after two transplants. The average total care cost of the 47 recovered cases was 11,336 RMB (range: 2,637-33,861 RMB). Due to the high burden of BCG lymphadenitis, especially in children with immunodeficiency, it is suggested that government departments should strengthen healthcare provider training, assign specific nurses to perform BCG vaccination, monitor vaccinated individuals actively and timely detect abnormal signals so as to reduce the incidence of BCG lymphadenitis.